Synthesis of meso-pyrrole-substituted corroles by condensation of 1,9-diformyldipyrromethanes with pyrrole - Temelli, Baris; Kapci, Pinar (Beilstein Journal of Organic Chemistry, 2022)
A copper triflate-mediated approach to access copper complexes of pyrrole-substituted corroles from the reaction of 1,9-diformyldipyrromethanes and an excess amount of pyrrole is presented for the first time. This procedure is a simple and efficient way for the preparation of corroles with a polymerizable substituent on meso-positions.
Keywords: corrole; dipyrromethane; macrocycles; metal triflates; pyrrole

(untitled) - Johnson, A. W.; Kay, I. T. (Proc. Chem. Soc., London, 1964)

(untitled) - Johnson, A. W.; Kay, I. T. (J. Chem. Soc., 1965)

(untitled) - Paolesse, R. (Synlett, 2008)

(untitled) - Aviv-Harel, I.; Gross, Z. (Chem. – Eur. J., 2009)

(untitled) - Ji, W.; Wang, T.-X.; Ding, X.; Lei, S.; Han, B.-H. (Coord. Chem. Rev., 2021)

(untitled) - Jin, L.; Lv, S.; Miao, Y.; Liu, D.; Song, F. (ChemCatChem, 2021)

(untitled) - Fuhrhop, J.-H. (Langmuir, 2014)

(untitled) - Day, N. U.; Wamser, C. C.; Walter, M. G. (Polym. Int., 2015)

(untitled) - Di Natale, C.; Gros, C. P.; Paolesse, R. (Chem. Soc. Rev., 2022)

(untitled) - Friedman, A.; Landau, L.; Gonen, S.; Gross, Z.; Elbaz, L. (ACS Catal., 2018)

(untitled) - Zhao, Y.; Dai, W.; Peng, Y.; Niu, Z.; Sun, Q.; Shan, C.; Yang, H.; Verma, G.; Wojtas, L.; Yuan, D.; Zhang, Z.; Dong, H.; et al. (Angew. Chem., Int. Ed., 2020)

(untitled) - Brandès, S.; Quesneau, V.; Fonquernie, O.; Desbois, N.; Blondeau-Patissier, V.; Gros, C. P. (Dalton Trans., 2019)

(untitled) - Zhao, Y.; Peng, Y.; Shan, C.; Lu, Z.; Wojtas, L.; Zhang, Z.; Zhang, B.; Feng, Y.; Ma, S. (Nano Res., 2022)

(untitled) - Gryko, D. T.; Koszarna, B. (Org. Biomol. Chem., 2003)

(untitled) - Paolesse, R.; Nardis, S.; Sagone, F.; Khoury, R. G. (J. Org. Chem., 2001)

(untitled) - Gryko, D. T.; Jadach, K. (J. Org. Chem., 2001)

(untitled) - Decréau, R. A.; Collman, J. P. (Tetrahedron Lett., 2003)

(untitled) - Geier, G. R., III; Grindrod, S. C. (J. Org. Chem., 2004)

(untitled) - Braaten, K. C.; Gordon, D. G.; Aphibal, M. M.; Geier, G. R., III (Tetrahedron, 2008)

(untitled) - Geier, G. R., III; Chick, J. F. B.; Callinan, J. B.; Reid, C. G.; Auguscinski, W. P. (J. Org. Chem., 2004)

(untitled) - Guilard, R.; Gryko, D. T.; Canard, G.; Barbe, J.-M.; Koszarna, B.; Brandès, S.; Tasior, M. (Org. Lett., 2002)

(untitled) - Ooi, S.; Tanaka, T.; Osuka, A. (Eur. J. Org. Chem., 2015)

(untitled) - Sankar, J.; Anand, V. G.; Venkatraman, S.; Rath, H.; Chandrashekar, T. K. (Org. Lett., 2002)

(untitled) - Temelli, B.; Gündüz, M.; Yüksel, D. (Tetrahedron, 2018)

(untitled) - Temelli, B.; Kalkan, H. (Beilstein J. Org. Chem., 2018)

(untitled) - Temelli, B.; Ozasik, O.; Yüksel, D. (Eur. J. Org. Chem., 2017)

(untitled) - Temelli, B.; Kalkan, H. (Synth. Commun., 2018)

(untitled) - Gryko, D. T. (Eur. J. Org. Chem., 2002)

(untitled) - Gryko, D. T.; Fox, J. P.; Goldberg, D. P. (J. Porphyrins Phthalocyanines, 2004)

(untitled) - Nardis, S.; Monti, D.; Paolesse, R. (Mini-Rev. Org. Chem., 2005)

(untitled) - Gryko, D. T. (J. Porphyrins Phthalocyanines, 2008)

(untitled) - König, M.; Faschinger, F.; Reith, L. M.; Schöfberger, W. (J. Porphyrins Phthalocyanines, 2016)

(untitled) - Brückner, C.; Posakony, J. J.; Johnson, C. K.; Boyle, R. W.; James, B. R.; Dolphin, D. (J. Porphyrins Phthalocyanines, 1998)

(untitled) - Ryppa, C.; Senge, M. O.; Hatscher, S. S.; Kleinpeter, E.; Wacker, P.; Schilde, U.; Wiehe, A. (Chem. – Eur. J., 2005)

(untitled) - Rohand, T.; Dolusic, E.; Ngo, T. H.; Maes, W.; Dehaen, W. (ARKIVOC, 2007)

(untitled) - Taniguchi, M.; Balakumar, A.; Fan, D.; McDowell, B. E.; Lindsey, J. S. (J. Porphyrins Phthalocyanines, 2005)